Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.29303/jppipa.v8i6.2306
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physical Resistance of Apple Tomatoes After Exposed to A Magnetic Field Extremely Low Frequency (ELF) Intensity 600 µT and 1000 µT

Abstract: Apple tomatoes with the scientific name Lycopersicum Pyriporme can last 7 days at room temperature and 14 days if stored in the refrigerator. The purpose of this study was to examine the effect of the ELF magnetic field intensity 600 uT and 1000 uT for 30, 60 and 90 minutes on the degree of acidity (pH), density (ρ) and physical quality of apple tomatoes. The research design used was RAL (completely randomized design). Data collection on the pH variable begins with crushing the tomatoes and then measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Aplikasi paparan medan magnet telah diterapkan dalam beberapa bidang kehidupan, salah satunya bidang pertanian. Berbagai penelitian telah dilakukan tentang pengaruh paparan medan magnet terhadap pertumbuhan guna meningkatkan produktifitas tanaman memberikan pengaruh positif pada perkecambahan biji pada beberapa jenis tanaman seperti kacang hijau (Sari et al, 2015), sorghum oleh Lazim dan Nasur (2017), gandum (Gholami et al, 2010), jintan putih (Samani et al, 2013), kentang ( El-Ghizawy et al, 2016), jelatang (Rostami et al, 2014), lemon balm (Ulgen, 2017), bunga matahari (Matwijczok et al, 2012) dan bawang (Hozayn et al, 2015).…”
Section: Pendahuluanunclassified
“…Aplikasi paparan medan magnet telah diterapkan dalam beberapa bidang kehidupan, salah satunya bidang pertanian. Berbagai penelitian telah dilakukan tentang pengaruh paparan medan magnet terhadap pertumbuhan guna meningkatkan produktifitas tanaman memberikan pengaruh positif pada perkecambahan biji pada beberapa jenis tanaman seperti kacang hijau (Sari et al, 2015), sorghum oleh Lazim dan Nasur (2017), gandum (Gholami et al, 2010), jintan putih (Samani et al, 2013), kentang ( El-Ghizawy et al, 2016), jelatang (Rostami et al, 2014), lemon balm (Ulgen, 2017), bunga matahari (Matwijczok et al, 2012) dan bawang (Hozayn et al, 2015).…”
Section: Pendahuluanunclassified
“…Exposure to ELF magnetic fields with intensities of 60 mT for 20 minutes on tomato seeds, significantly affected to reduce acid bacteria activity, hence inhibiting putrefactive microorganism activity on foodstuffs associated with rising and decreasing average pH values (Nur et al, 2022), and the intensity of 1 mT, 2 mT, and 3 mT can increased the chlorophylls level for low magnetic flux density and low exposure duration (Racuciu, 2020). Exposure to the ELF magnetic field intensity of 600 µT for 60 minutes had the potential to maintain the physical quality of apple tomatoes (Sudarti et al, 2022). Exposure to an ELF magnetic field intensity of 300 µT for 120 minutes has a significant effect on edamame plant biomass (Prihatin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A magnetic field strength of 900 µT can help preserve the vitamin C content in red wine by suppressing the growth of harmful bacteria (Sudarti et al, 2022c). Research has demonstrated that being exposed to an extremely low frequency (ELF) magnetic field with an intensity of 1000 µT can effectively preserve the freshness of apple tomatoes by preventing the growth of harmful bacteria (Sudarti et al, 2022d). Another study says that the effective dose for inhibiting the activity of lactic acid-forming bacteria in green cayenne pepper was an exposure intensity of 500 µT for 120 minutes (Nuriyah & Sudarti, 2022).…”
Section: Introductionmentioning
confidence: 99%